2020
DOI: 10.1620/tjem.251.279
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative In-Hospital Rehabilitation Improves Physical Function in Patients with Pancreatic Cancer Scheduled for Surgery

Abstract: Low preoperative physical function in cancer patients is associated with postoperative complications; however, there have been no reports on the benefits of in-hospital preoperative rehabilitation on preoperative physical function in patients with pancreatic cancer. Therefore, the aim of this study was to quantitatively determine the effects of preoperative in-hospital rehabilitation provided under the supervision of a physiotherapist, on preoperative physical function in patients with pancreatic cancer. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…We first demonstrated that physical therapy increased the FIM score in patients with HCC. In previous studies, physical therapy has been reported to increase the FIM score in patients with various cancers, including colorectal cancer [10] and pancreatic cancer [36]. Thus, our results are in good agreement with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…We first demonstrated that physical therapy increased the FIM score in patients with HCC. In previous studies, physical therapy has been reported to increase the FIM score in patients with various cancers, including colorectal cancer [10] and pancreatic cancer [36]. Thus, our results are in good agreement with these previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…The rate of retention (50%) at week 12 is lower than previous trials of supervised exercise training in PanCa (10,11,45). This is not unexpected as the patients included in those trials were highly selected having already completed pancreatic resection (10,45), or only a shorter-term in-hospital program (~12 d) was used (11). Comparison of the other adherence metrics (i.e., rates of mean attendance, exercise interruption, and dose modification) with the relevant trials in PanCa (10,11,45) is hindered by their absence of reporting of equivalent data.…”
Section: Discussioncontrasting
confidence: 56%
“…In a recent systematic review by our team (9), we identified only seven separate trials involving only 201 patients with over half being case reports or case series. Although a few trials (10,11) have been reported since our review also favoring exercise in PanCa, there has been no evidence from a setting where broader inclusion criteria and more flexible programs are used as compared with clinical trials under tightly controlled conditions (i.e., explanatory trials).…”
mentioning
confidence: 92%
“…To date, there are only seven individual published studies focusing exclusively on patients with PanCa. [22][23][24] Of them, only three studies (all without control) have been conducted in patients during NAT (including one single-arm study, 53 one case series 25 and one case report. 26 In addition, among the ongoing exercise trials for patients with PanCa in ClinicalTrial.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Despite the benefits associated with exercise in cancer management, only seven exercise trials have been undertaken in patients with PanCa with over half being case reports or a case series. [22][23][24] Although a recent systematic review by our team found that exercise may be safe and feasible in patients with PanCa, 24 most of the patients enrolled in the studies were highly selected having already successfully completed NAT and surgical resection. Additionally, a case series 25 and a case report 26 of patients with borderline resectable or locally advanced PanCa during NAT performing supervised exercise training showed promising results that warrant further investigation with a more rigorous study design.…”
Section: Introductionmentioning
confidence: 99%